Perfil de citocinas e desfecho clínico de pacientes coinfectados HIV e Leishmania spp - COSTA, Larissa Di Leo Nogueira (2022)
Visceral leishmaniasis (VL) is an endemic parasitic disease in Latin America, and its clinical picture is aggravated in co-infections with human immunodeficiency virus (HIV). In these patients, a complex immune response is observed, with correlation of pro-, anti-inflammatory and modulating cytokines. The aim of this study is to identify the profile of inflammatory cytokines and the outcomes presented by VL/HIV coinfected patients. A prospective, longitudinal study was conducted from January 2013 to July 2020 among 169 patients coinfected with VL and HIV. The outcomes investigated were the occurrence of VL relapse, hospital death of coinfected patients, and the clinical presentation of coinfected patients. For statistical analysis, the Chi-square test, the Mann-Whitney test and Oddis Ratio measurements were performed. As main results, in the present study the occurrence rates were 41.4% for VL relapse and 5.5% for death. Splenomegaly and adenomegaly were associated with increased risk of VL relapse. Weight loss and edema were associated with increased risk of death. Patients with relapse had higher levels of urea (P = .005) and creatinine (P < .001). Patients who died had lower red blood cell (P = .012), hemoglobin (P = .017), and platelet (P < .001) counts. Among the sample of 169 coinfected patients, 50 patients were separated by primary sample separation to perform blood sample collection and analyzed for cytokine release. It was observed that there was a statistically significant difference in IL-2 and IL-10 production between the groups. Furthermore, in co-infected patients there is a moderate or strong and statistically significant positive correlation in the production of IL-2 and IL-4; IL-2 and IL-6; IL-4 and TNF; IL-4 and IL-6; IL-6 and TNF. The results suggest that clinical and laboratory factors show associations with the outcomes of VL relapse and death in VL/HIV coinfected patients, however, there was no association of the cytokines produced with the clinical presented.